The Reasons for Disinterest of Primary Level Students for Schools in Helmand Lashkargah City (American Journal of Education and Technology, 2025)
According to instructors who increasingly feel that students are losing interest in their studies and their awareness of their authority, a teaching-learning process would not be considered efficient and effective if it consisted solely of the transfer of knowledge without appropriate reception. The aim of this study was to determine the factors that may contribute to students’ lack of excitement in primary-level students learning. And find the beast methods for the solution of this problem. The study was conducted in Helmand, Lashkargah City. Two schools (Shaheed Engineer Abdul Matin High and Meddle) were easily used to choose 10 primary level students randomly selected from among 200 students. And their parents were randomly selected to represent the reasons and disinterest of the students in schools. The research participants in this descriptive research approach were used to collect data. The main source of data for this study was collected through self-administered questionnaires, interviews, and direct observations. after data analysis, it was determined that a number of factors contributed to the disinterest of students in primary-level schools, including parents’ lack of involvement with their children, homework refusal, shortage of access to classroom supplies, the distance between home and school, lack of student transportation, a shortage of professional teachers in schools, students’ lack of work during class, lack of time for entertainment, and disregard for each student’s unique interests and desires. It is advised that parents provide their children with the tools they need to finish their schoolwork, and the government builds new schools in nearby or distant locations.